An Analysis of Students’ Reading Comprehension in Narrative Text - Mulyadin , Asrul (Yayasan Pendidikan Internasional Bengkulu, 2023)
This research was conducted to analyze students' reading comprehension of narrative texts. A qualitative descriptive method with observations, interviews, and documentation is utilized as instruments. The results showed that students had a variety of abilities in understanding narrative texts, from the interviews and existing observational data. Moreover, it was found that 16 students understood this material because they could explain the meaning, cite the examples, mention the general structure, and determine the general structure of narrative texts in the text entitled